LITERACY AND LANGUAGE TEACHING - Sapta Mei Budiyanto (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2013)
The main target and goal of this writing is to show the information of global demographic andtechnological changes that has happened so rapidly in both domestic and international arenas,therefore, the society should effort seriously in order that they can adapt easily. As everybodyknows, that the development of science, knowledge, and technology is so fast, excelencent, and amazing,they never thought before that it is beyond their imagination.Society/people should enlarge and enrichtheir sience and knowledge for anticipating of cultural and technological shock, if not, they will be leftbehind, so far and so primitive in this modern era.